Case report: Early-onset Parkinson's disease with initial spastic paraparesis and hyperreflexia caused by compound heterozygous PRKN-gene exon 2 and 4 deletions - Jensen, Ida; Hendrich, Corinna; Klietz, Martin; Berding, Georg; Höglinger, Günter U.; Wegner, Florian (Frontiers in Neurology, 2022)
Pathogenic variants in the Parkin-gene (PRKN) are among the most common genetic causes for Early Onset Parkinson´s disease (EOPD). Patients with EOPD can present with atypical clinical features and misdiagnosis is frequent. Here, we report a clinical phenotype with atypical signs and symptoms of a 35-year-old male patient with EOPD caused by a compound heterozygous PRKN-gene deletion of exons 2 and 4. After initial diagnosis of stiff person syndrome the patient was admitted to our department for a second opinion after eight years of untreated disease progression. He presented with prominent spastic paraparesis pronounced on the right side and hyperreflexia as well as Parkinsonism with rigidity predominantly affecting the upper limbs, bradykinesia and resting tremor. In the diagnostic assessment, magnetic evoked potentials to the anterior tibial muscles showed a low amplitude on the right side, compatible with pyramidal tract disturbance. However, MRI of the head and the spine did not show any pathologies or atrophy. A [123I] FP-CIT SPECT scan revealed profoundly and left-pronounced reduced striatal uptake suggesting a neurodegenerative Parkinson syndrome. Even though an acute levodopa challenge did not show marked improvement of symptoms, the chronic levodopa challenge with up to 450 mg/day significantly reduced the rigidity and bradykinesia. Surprisingly, spastic paraparesis and hyperreflexia diminished under dopaminergic treatment. Finally, genetic analysis by next generation sequencing confirmed compound heterozygous deletions of exon 2 and 4 in the PRKN-gene. As presented in this case, the awareness for atypical clinical symptoms of EOPD is essential to prevent misdiagnosis in young patients.